Chronic energy deficiency (CED) and maternal diet is related to stunting incidence - Rosita Rosita; Lina Fitriani; Dyah Tahir; Yenni Yenni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: One of the main causes of stunting is the lack of continuous energy intake in women of childbearing age (from adolescence, pre-conception to pregnancy) which results in Chronic Energy Deficiency during pregnancy which begins with the occurrence of